IgLON5-Associated Encephalitis With Atypical Brain Magnetic Resonance Imaging and Cerebrospinal Fluid Changes - Montagna, Massimiliano; Amir, Rizvana; De Volder, Ilse; Lammens, Martin; Huyskens, Jef; Willekens, Barbara (Frontiers in Neurology, 2018)
IgLON5-associated encephalitis is a syndrome with different clinical presentations consisting of sleep dysfunction, bulbar dysfunction, chorea and progressive supranuclear palsy-like symptoms whereas dysautonomy and cognitive decline usually appear in later stages of the disease. We report a case of a patient with IgLON5-associated encephalitis presenting with rapidly progressive cognitive decline and atypical inflammatory lesions on brain magnetic resonance imaging, oligoclonal bands on cerebrospinal fluid, anti-IGLON5 antibodies exclusively of the IgG1 class and a fierce inflammatory reaction on brain biopsy, who responded favorably to immunotherapy.